Cultural Origins of Risk Taking in Financial Markets - Ek, Andreas; Gokmen, Gunes; Majlesi, Kaveh (Journal of Financial and Quantitative Analysis, 2026)
This article studies how cultural heritage influences the differences in risk taking in financial markets. We combine data on the asset allocation of second-generation immigrants in Sweden with risk-taking culture in their parents’ countries of origin. We find that descendants of risk loving cultures are more likely to participate in equity markets, and, conditional on participation, allocate a larger share of financial wealth to equities. Moreover, they take on more idiosyncratic risk by favoring directly held stocks over mutual funds and forming more volatile portfolios. These findings are not driven by selective migration or other country of origin characteristics.